Gambogic acid-loaded magnetic Fe3O4 nanoparticles inhibit Panc-1 pancreatic cancer cell proliferation and migration by inactivating transcription factor ETS1 - Wang C (Dove Medical Press, 2012)
Cailian Wang1, Haijun Zhang1, Yan Chen1, Fangfang Shi1, Baoan Chen2,31Department of Oncology, 2Department of Hematology, Zhongda Hospital, 3Faculty of Oncology, Medical School, Southeast University, Nanjing, People’s Republic of ChinaBackground: E26 transformation-specific sequence-1 (ETS1) transcription factor plays important roles in both carcinogenesis and the progression of a wide range of malignancies. Aberrant ETS1 expression correlates with aggressive tumor behavior and a poorer prognosis in patients with various malignancies. The aim of the current study was to evaluate the efficacy of a drug delivery system utilizing gambogic acid-loaded magnetic Fe3O4 nanoparticles (GA-MNP- Fe3O4) on the suppression of ETS1-mediated cell proliferation and migration in Panc-1 pancreatic cancer cells.Methods: The effects caused by GA-MNP- Fe3O4 on the proliferation of Panc-1 pancreatic cancer cells were evaluated using a MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay while inhibition of tumor cell migration was investigated in a scratch assay. The expressions of ETS1, cyclin D1, urokinase-type plasminogen activator (u-PA), and VEGF (vascular endothelial growth factor) were examined by Western blot to elucidate the possible mechanisms involved.Results: In Panc-1 pancreatic cancer cells, we observed that application of GA-MNP- Fe3O4 was able to suppress cancer cell proliferation and prevent cells from migrating effectively. After treatment, Panc-1 pancreatic cancer cells showed significantly decreased expression of ETS1, as well as its downstream target genes for cyclin D1, u-PA, and VEGF.Conclusion: Our novel finding reaffirmed the significance of ETS1 in the treatment of pancreatic cancer, and application of GA-MNP- Fe3O4 nanoparticles targeting ETS1 should be considered as a promising contribution for better pancreatic cancer care.Keywords: ETS1 transcription factor, gambogic acid, pancreatic cancer, magnetic nanoparticles